Sudden Cardiac Death: Clinical Updates and Perspectives - Schupp, Tobias; Behnes, Michael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Sudden cardiac death (SCD) affects more than four million patients per year worldwide, and accounts for up to 50% of all cardiovascular deaths. Related to the improved treatment options for cardiovascular diseases during the past several decades (e.g., improved guideline adherence to pharmacotherapies, increasing supply with cardiac devices, and better revascularization strategies), the characteristics of patients presenting with SCD have significantly changed, making risk prediction for SCD even more complex. The present Special Issue reprint addresses the prognostic impact of patients' characteristics (such as body mass index), airway and ventilation management in patients needing cardiopulmonary resuscitation, and the prognostic value of a targeted ambulance treatment quality improvement programme. Furthermore, the prognostic value of blood-derived biomarkers and cardiac pharmacotherapies for the prevention of SCD was investigated.